(untitled) (Ciencias de la Ingeniería y Aplicadas, 2018)
The work shows the updating of the mining cadastre in a filling quarry of the “Comandante Ernesto Che Guevara” factory, using satellite images and the electronic tablet as a tool to obtain field information. The process for the cadastral update was structured in seven steps for its implementation: first, the high-resolution images to be used (HRS) are selected to cover the entire area to be worked on; second, the photo control process (CF) is carried out, from these photo control points (PCF) their X, Y, Z coordinates are taken; third, an orthorectified image is created to correct the geometry of some elements that cause inaccuracies; fourth, comparison of the orthoimage and the cadastral map; Fifth, during the rectification of the plots corresponding to the infill quarry, the layers are superimposed and the boundaries of the quarry plots on the map are matched with those on the satellite image and adjusted if necessary. All updated data in the image is taken to the cadastral software in the sixth step. Finally, the modified layers are activated and the tables are updated with the corresponding alphanumeric data. The method shown allows for agile maintenance of the cadastre or GIS, increases the precision of cadastral updating work and its productivity, reduces work time, simplifies direct surveys in the field and achieves greater automation in the processes related to the mining cadastre.